Effect of Different Levels of Protein Supplementation on Reproductive Performance of Rabbit Does Under Tropical Conditions - Salma, Ummay; Miah, Abdul Ghaffar; Z. H., Khandaker; Reza, Abidur (Universiti Putra Malaysia Press, 2002)
The study was conducted over a 125 days period with 150 does which were randomly assigned to three treatment groups of 50 does each. The does were fed one of the diets containing 13.17, 16.64 and 21.00% crude protein (CP) supplementation with ad libitum green grass (Hymenachne pseudointerrupta, CP=6.6%). Gestation period, litter size & litter weight ( at birth & weaning), individual pup weight at birth and weight gain up to weaning (28 d) did not differ (P>0.05) among the treatment groups. The pregnancy rate of does and mortality of pups up to weaning were significantly affected (P<0.05) among the treatment groups. The mean of the pregnancy rate was highest (100 %) in the group fed on 21.00% CP diet, while the number of pups alive up to weaning was highest (100 %) in the group fed on 13.17% CP diet. Based on these findings, the inclusion of 21.00% CP diet along with ad libitium green grass may be suggested for better reproductive performance of does under tropical conditions.